Genealogical Researches of Karpiai Family: the Possibilities Evaluation of Prosopography Researches - Pangonytė, Rugilė (Bibliotheca Lituana, 2019)
Karpiai – a famous noble family of the Grand Duchy of Lithuania – are distinguished by their political and educative activities. The family’s influence is most markedly observed in the 18th–19th centuries, when the most famous and active members of the Karpiai family had lived. This family has not received plenty of scholarly attention, though from time to time new studies do spring up. Almost all of them are oriented to analyzing the activities of separate members of the Karpiai family, while the family’s origin and genealogy researches are scarce. Recently, prosopography has been found to be a very promising method for analyzing noble families. It analyzes the person, their environment, social position, career, power amassment, political influence, and other factors, researching bonds between individuals and constantly evaluating them in an interplay aspect. Besides, in prospect, a prosopographic analysis creates an ideal base for a person’s historical biographical research. This article returns to the beginning of the Karpiai family, studies the theories regarding its legendary origin and the appearance of their progenitor’s in the Grand Duchy, and explains how the recent researches of the Karpiai family’s origin lay the foundation for productive prosopographic researches. Since in prosopography one of the most important methods is the genealogical one, this article discusses the topic of genealogical tree researches of the Karpiai family.